협업 소프트웨어 분석을 통한 디자인 협업의 가능성 제안 - 백경화; Baek Kyoung Hwa; 하은아; Ha Euna (기초조형학연구, 2018)
사용자들 간의 커뮤니케이션 방식이 다양해지고 급변하는 환경에서 온라인상의 원활한 커뮤니케이션을 바탕으로 협업을 가능하게 하는 소프트웨어의 개발이 발전을 거듭하고 있다. 이에 온라인 협업 소프트웨어의 현재 기술적 상황과 특성을 파악하여, 협업이 필수 불가결한 디자인 분야에서 활용할 수 있는 디자인 협업 소프트웨어의 가능성을 찾는 것을 목적으로 한다. 연구방법은 현재 시장에서 활용이 잘되고 있는 온라인 협업 소프트웨어를 유형별로 분류하고 각 특성을 비교·분석하였다. 온라인 협업 소프트웨어의 특성 분석은 유형별로 구분하였는데, 분류는 SaaS와 B2B 소프트웨어 리뷰 전문 업체인 파이낸스온라인(financesonline)의 보고서 내용을 기준으로 삼았다. 유형은 세 가지로 분류했는데 첫째, 구성원 간의 인스턴트 메시지와 채팅 기능에 집중되는 커뮤니케이션(communication) 유형, 둘째, 서로 다른 공간에 있는 참여자들이 실시간 대화를 통한 의견 교환 및 의사결정 하는 컨퍼런싱(conferencing) 유형, 셋째, 원활한 협업을 위해 프로젝트 진행 과정을 종합적으로 관리하는 코디네이션(coordination) 유형이다. 해당 문헌 자료와 선행연구를 기본으로 하되 최신경향이 반영된 IT전문 기사와 경제연구소의 보고서 등도 참고하였다. 연구의 결과 디자인 협업을 가능하게 하는 소프트웨어는 다음과 같은 내용을 반영해야 한다. 첫째, 시각적 이미지가 커뮤니케이션의 중심이 되는 이미지 기반의 의견공유가 쉽게 이루어져야 한다. 둘째, 디자인 프로세스를 진행하면서 변경·수정되는 최신의 자료를 체계적으로 보여주어 협업으로 인한 정보의 혼란이 없어야 한다. 셋째, 디자이너들이 사용하는 다양한 프로그램이 외부 프로그램과의 자연스러운 연동으로 디자인 작업이 효율적으로 운용될 수 있어야 한다. 넷째, 협업의 작업과 개인적 디자인 작업을 구분할 수 있어 공유·협업을 디자이너가 선택적이고 주체적으로 활용할 수 있어야 한다. In a rapidly changing environment where communication methods between users vary, software that enables collaboration based on the smooth communication on the internet is being developed. Therefore, the purpose of this study is to observe current technical situation and features of on-line collaboration software to find out the possibility of design collaboration software that can be employed in design field where collaboration is indispensable. As a research method, online collaborative softwares which are well used in the market are classified by type for comparative analysis. Based on the literature and previous researches, IT articles and economic research reports reflecting the latest trends were also referred. As a result, software that enables design collaboration should reflect the followings. First, image based opinion sharing should be easy which is the center of communication. Second, systematically show the latest data that is changed and modified in the design process so that there is no confusion of information due to collaboration. Third, various programs used by designers should be naturally interlocking with external programs to operate design work efficiently. Fourth, it is necessary to be able to distinguish between collaborative work and personal design work so that designers can utilize shared and collaborative options selectively and independently. Fourth, designers should be able to selectively utilize shared and collaborative work by making it possible to distinguish collaboration work from personal design work.